The Reproduction of Urban Capitalism: Street Food and the Working Day in Colonial Mombasa. (March 2023) - Smart, Devin
Abstract: This article argues that street food was an essential part of the social reproduction of Mombasa's working class during the colonial period. Like in other expanding capitalist cities, as Mombasa grew, urban workers lived further from their place of employment, which meant they could not return home for their midday meal. Street-food vendors provided them lunch at low prices in convenient locations, and therefore reproduced the working day by provisioning the calories that bridged morning to afternoon. However, postwar municipal authorities also wanted to create a particular kind of urban society in which the 'informal' activities of street-food vendors did not fit, and tried to expel them from the city's streets. As these campaigns unfolded, an unresolved contradiction emerged between this elite view of Mombasa, and the reality that the services vendors provided were necessary for the reproduction of the city's economy.